Deixis and alignment : inverse systems in indigenous languages of the Americas - Zúñiga, Fernando (Typological studies in language ;, 2006)
This book proposes a notion of inverse that differs from two widespread positions found in descriptive and typological studies (one of them restrictive and structure-oriented, the other broad and function-centered). This third stance put forward here takes both grammar and pragmatic functions into account, but it also relates the opposition between direct and inverse verbs and clauses to an opposition between deictic values, thereby achieving two advantageous goals: it meaningfully circumvents one of the usual analytic dilemmas, namely whether a given construction is passive or inverse, and it.